Definition of a parallel execution model with abstract state machines - Németh, Zsolt (Acta Cybernetica, 2002)
Languages, architectures and execution models are strongly related. A new architectural platform makes necessary to modify the execution model in order to exploit all the advantages of the underlying architecture while preserving its main characteristics. The latter issue requires a careful analysis of the design process. Abstract State Machines offer a powerful method for aiding complex system design. In this paper some aspects of its applicationare presented by taking the redesign process of a parallel Prolog model as an example.